Current tests for diagnosis of hepatitis B virus infection and immune responses of HBV-related HCC - Wanting Shi; Kang Li; Yonghong Zhang (Frontiers in Oncology, 2023)
Chronic hepatitis B virus (HBV) infection is a worldwide public health threat that results in huge morbidity and mortality. Late diagnosis and delayed treatment of HBV infections can cause irreversible liver damages and occurrence of cirrhosis and hepatocellular carcinoma (HCC). Detection of the presence and activity of HBV are the cornerstones of diagnosis and management in HBV related disease. Moreover, comprehensive knowledge of the mechanisms regulating HBV immunobiology is pivotal for managing diseases related with HBV. Here we tried to categorize and illustrate the classical and novel approaches used for diagnosis of HBV. Also, we reviewed our current knowledge on the immunobiology of HBV related HCC.